Factors Influencing the Incidence of Preeclampsia at Tiley Health Center - Praise Astuti Mahmud; Reny Retnaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Preeclampsia is a pregnancy complication that contributes significantly to maternal and perinatal morbidity and mortality, especially in developing countries. Despite various preventive measures, preeclampsia is still frequently found at the primary health care level. This study aims to analyze the factors influencing the incidence of preeclampsia in pregnant women at the Tiley Care Community Health Center. This study used an observational analytical design with a cross-sectional approach. The study population was all pregnant women who visited antenatal care at the Tiley Care Community Health Center, with a sample of 60 respondents selected using a total sampling technique. Data were collected through a review of medical records and KIA books, then analyzed univariately and bivariately using the Chi-Square test with a significance level of α = 0.05. The results showed that maternal age, history of hypertension, nutritional status based on body mass index, and adherence to antenatal care visits had a statistically significant relationship with the incidence of preeclampsia. Meanwhile, parity did not show a significant relationship with the incidence of preeclampsia. This study concluded that the incidence of preeclampsia is influenced by various maternal factors and maternal health behaviors during pregnancy. These findings underscore the importance of implementing risk-based antenatal care through early screening, ongoing monitoring, and increased adherence to antenatal care visits as a preventative measure for preeclampsia at the primary healthcare level.